Viropolitics and capitalistic governmentality: On the management of the early 21st century pandemic - Ayala-Colqui, Jesús (2020)
This text offers an analysis of the power apparatuses (dispositifs) employed in the management of the early 21st century Covid-19 pandemic. The paper is divided into two sections. The first part is oriented both towards a characterization of the mode of government that preceded the onset of the viral disease and towards an exposition of the power apparatuses it instrumentalized. This mode of government is referred to in the text as «capitalistic govermentality», a practice combining regimes of knowledge, economically encoded materialities, subjective formations and power apparatuses in order to maintain the valorization of private capital. The second part exposes the ways in which the apparatuses of capitalistic governmentality are modified and articulated in the context of the pandemic, through a phenomen given the provisional name of «viropolitics».